Three-dimensional aortic arch geometry and blood flow in neonates after surgical repair for aortic coarctation - Fricke, Katrin; Christierson, Lea; Heiberg, Einar; Sjöberg, Pia; Hedström, Erik; Steiner, Kristoffer; Weismann, Constance G.; Töger, Johannes; Liuba, Petru (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRecurrent coarctation of the aorta (re-CoA) is a well-known although not fully understood complication after surgical repair, typically occurring in 10%–20% of cases within months after discharge.ObjectivesTo (1) characterize geometry of the aortic arch and blood flow from pre-discharge magnetic resonance imaging (MRI) in neonates after CoA repair; and (2) compare these measures between patients that developed re-CoA within 12 months after repair and patients who did not.MethodsNeonates needing CoA repair, without associated major congenital heart defects, were included. Transthoracic echocardiography (echo) and 4D phase-contrast MRI were performed prior to discharge after CoA repair to assess 3D arch geometry, flow velocity and flow pattern in the distal aortic arch corresponding to the area at risk for re-CoA. Arch geometry was assessed by measuring angles of the aortic arch and its branches using 3D patient-specific geometries segmented from MRI. Continuous data are presented as median and interquartile range.ResultsThe median age at CoA surgery was 9 days. Four out of the included 28 patients (14%) developed re-CoA within the first 12 months after surgery. Re-CoA was associated with repair technique (lateral thoracotomy 100% vs. 33%, p = 0.02), higher postoperative isthmic flow velocity by echocardiography (1.9 [0. 9] m/s vs. 1.25 [0.5] m/s, p = 0.04) and postoperative crenel aortic arch (100% vs. 21%, p = 0.007) with a larger distance between the first and last branching points (12.6 [3.1] mm vs. 7.3 [7.0] mm; p = 0.01). A smaller angle between the ascending aorta and the brachiocephalic artery (89 [58]° vs. 122 [37]°, p = 0.05) and between the proximal aortic arch and the left carotid artery (75° vs. 97 [37]°, p = 0.04), with a more pronounced caliber change between the ascending aorta and the proximal (1.85 vs. 0.86 [0.76]; p = 0.03) and distal aortic arch (2.19 [2.42] vs. 1.01 [0.94]; p = 0.03) were observed in re-CoA patients. Patients who developed re-CoA had more left-handed helical flow in systole (p = 0.045), more right-handed helical flow in diastole (p = 0.02), and less vortical flow (p = 0.05).ConclusionSubtle changes in aortic arch geometry and flow pattern early after neonatal CoA repair may contribute to the risk of re-CoA.